Increasing Distributed Generation Hosting Capacity in Distribution Networks: A CO2 Emission Analysis - Melgar-Dominguez, Ozy D. [UNESP]; Mantovani, Jose R. S. [UNESP]; Pourakbari-Kasmaei, Mandi; Lehtonen, Matti; IEEE (Ieee, 2020)
This work aims at proposing a strategy based on an environmental and technical perspective to assess the amount of distributed generation (DG) that can be deployed into an electric distribution network (EDN). The presented approach seeks to minimize the carbon emissions and energy losses while the installed capacity of renewable DG units is maximized. To enable the DG integration without requiring EDN upgrading, the operations of capacitor banks (CBs) and voltage regulators (VR) devices are optimized simultaneously. To analyze the relationship between the installed DG and demand consumption, the effects of voltage-dependent loads are investigated. Several test cases are studied in a 42-node distribution network. Results show that by applying operating actions and determining the hosting capacity of the EDN for deploying DG units, environmental and technical benefits could be achieved.
Keywords: DG hosting capacity; emissions reduction; exponential demand model